pH-Responsive Artesunate Polymer Prodrugs with Enhanced Ablation Effect on Rodent Xenograft Colon Cancer [Corrigendum] - Hao DL (Dove Medical Press, 2020)
Hao DL, Xie R, De GJ, et al. Int J Nanomed.  2020;15:1771– 1786. The authors have advised due to an error that occurred inadvertently at the time of figure assembly, the images of the cellular uptake of free C6 and ART-M1-C6 are incorrect for Figure 1 on page 1780.The authors have also advised on page 1779, Cytotoxicity Assay and Cellular Apoptosis Analysis section, second paragraph, the text “The apoptosis rates for cells treated with free ART, PBAE-ART4 and PBAE-ART2 for 24 h were 8.76%,  11.88% and 14.27%, respectively. After incubation for 72 h, the apoptosis rates were increased to 18.41%, 22.49% and  26.85%, respectively, with stronger apoptosis rates were observed in the micelles groups than that of free drug (Figure 2)” should read “The apoptosis rates for cells treated with free ART, PBAE-ART4 and PBAE-ART2 for 24 h were  8.73%, 11.84% and 14.23%, respectively. After incubation for 72 h, the apoptosis rates were increased to 18.35%,  22.42% and 26.76%, respectively, with stronger apoptosis rates were observed in the micelles groups than that of free drug (Figure 2).” The authors also advised that there is an error in Figure S2 of the supplementary material, the images of the CMC of PEOz-PLA-PBAE-2 and PEOz-PLA-PBAE-3 should be interchanged.The authors apologize for these errors and advise they do not affect the results and conclusions of the paper.Read the original article